Change of crop structure intensified water supply-demand imbalance in China’s Black Soil Granary - Ying Feng; Ying Guo; Yanjun Shen; Guangxin Zhang; Yanfang Wang; Xiaolu Chen (Agricultural Water Management)
Changes of crop planting area and structure generally cause much uncertainty in water sustainability. As the main grain producing area in China, the Black Soil Granary area (covering the whole Songhua River Basin) is facing the contradiction between water resources and grain production. Thus, assessing the effects of shifting crop areas and structures on water supply/demand is vital for ensuring China’s food security and sustainable water use in the region. This study used a decision tree model to extract crop distributions from 2000 to 2020, applied the Penman-Monteith model with crop coefficients to analyze water supply and demand changes, and identified key factors affecting crop water requirements. The results showed that: (1) from 2000 to 2020, the planting area continuously expanded, with a planting distribution of “soybean in the north, maize in the south, and rice in the vicinity of the river”. (2) The planting area of main crops increased by 81.12 % (77,514 km2), causing an additional water requirement of 5.93 billion m3 (+281.54 %). (3) Although precipitation increased in recent years, water shortages of crops continued to intensify due to the spatiotemporal mismatch with increase of crop water requirement. The expansion of the planting area has sharply increased local water demand and stress. Hence, it’s essential to study the spatial and temporal variations in agricultural water supply and demand in the basin, along with the effects of climate and planting structure changes. This will serve as a scientific basis for the rational allocation and sustainable utilization of water resources in the basin.